Koperasi Indonesia dan Permasalahannya - Mujiyanti, Sri Ayudha (Jurnal Informatika Ekonomi Bisnis, 2023)
The This article explores the challenges faced by cooperatives in Indonesia, focusing on human resources, capital, member awareness, societal perceptions, and competition. Despite significant growth, only 9.2% of the population are cooperative members, with a minimal contribution to the GDP and employment rate. The study aims to identify reasons hindering cooperative competitiveness and growth. Solutions include improving member training, capital management, transparency, and countering negative perceptions. Digital transformation can address competition from microfinance institutions and online platforms. Understanding these challenges will aid in developing effective strategies to strengthen cooperatives' role in Indonesia's economy.